Pengaruh Pembiayaan Mudharabah Dan Musyarakah Terhadap Profitabilitas Bank Umum Syariah Dengan Dana Pihak Ketiga (DPK) Sebagai Variabel Moderasi - Sapnah; Sagantha, Fitri (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
This study aims to determine the effect of Mudharabah and Musyarakah Financing on Profitability in Islamic Commercial Banks with Third Party Funds as a moderating variable. This research method is a quantitative research with an associative approach. The sample in this study is Islamic Commercial Banks that have been registered with the Financial Services Authority (OJK) in the 2020 - 2022 quarter period in the form of financial report data. Data collection was carried out using a purposive sampling method, so that a total of 48 samples were obtained from 4 Islamic Commercial Banks which could be processed. The analysis technique used in this study is multiple linear regression analysis and moderated regression analysis (MRA). The data is processed using the software application Eviews version 10. The partial test results show that (1) mudharabah financing has no significant effect on profitability with a probability value of 0.2602 > 0.05, (2) musyarakah financing has no significant effect on profitability with a probability value 0.8123 > 0.05. The simultaneous test results show that (3) mudharabah and musyarakah financing have a significant effect on profitability with a Prob (F-statistic) value of 0.000 <0.05. The MRA test results show that (4) third party funds are not able to moderate the effect of mudharabah financing on profitability with a probability value of 0.4993 > 0.05, (5) third party funds are unable to moderate the effect of musyarakah financing on profitability with a probability value of 0.1429 > 0.05.